2017
DOI: 10.3892/mmr.2017.7637
|View full text |Cite
|
Sign up to set email alerts
|

LDHA promotes tumor metastasis by facilitating epithelial-mesenchymal transition in renal cell carcinoma

Abstract: Previous studies have indicated that high expression of lactate dehydrogenase A (LDHA) exists in many human cancers. Recently, several reports showed that silencing or inhibition of LDHA could suppress metastasis of human cancer including renal cell carcinoma (RCC). However, the mechanism remains unknown. The role of LDHA in RCC migration and invasion was investigated using immunohistochemistry, western blotting, Transwell and scratch assays, and in vivo experiment. The influence of LDHA on the Warburg effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 30 publications
2
39
1
Order By: Relevance
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidence suggest that EMT promotes tumour metastasis in various cancers, including RCC [32][33][34][35][36][37]. Previous molecular analysis indicated that the high expression of AGK can induce the expression of HIF1a and promote EMT in cervical squamous carcinoma cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, as seen in Figure 3A , OPN mRNA levels significantly correlated with LDHA, which has been associated with the response to chemotherapy and tumor invasion. 19 , 20 Additionally, the knockdown of OPN using siOPN-1/siOPN-2 decreased LDHA protein levels ( Figure 3B ) and lactate production ( Figure 3C ) in NSCLC cell lines compared with cells treated with siNC. Finally, to verify lactate contributes to OPN caused CDDP resistance in NSCLC cells, the lactate treatment (5 mM, 24 hours) was found to increase NSCLC cells CDDP (5 µg/mL, 24 hours) resistance and partial rescue OPN-deficiency led CDDP sensitivity ( Figure 3D ).…”
Section: Resultsmentioning
confidence: 92%
“…According to the results of GO and KEGG enrichment analysis, key module genes were primarily enriched in cell adhesion and ECM function regulation. Recent studies reported that LDHA can promote the progression of renal cell carcinoma and bladder cancer by promoting EMT (29,30). Moreover, lactate, the ultimate metabolite of aerobic glycolysis, led to an acidic tumor microenvironment that facilitated the degradation of ECM and the production of actin filaments (31).…”
Section: Discussionmentioning
confidence: 99%